Effects of Thorium Dioxide upon Blood Clotting and Platelets. I. In Vitro Studies - Hjort, P. F; McGehee, W. G; Rapaport, S. I (Thrombosis and Haemostasis, 1966)
Thorium dioxide was found to damage clotting factors and to interfere with platelet functions in vitro:1. Fibrinogen and factor V were progressively inactivated. Citrate did not prevent damage to these factors. Thorium dioxide was concentrated in the clot, which suggests that it binds to fibrinogen.2. Factors II, VII, IX, and X were also inactivated. Inactivation of these factors could be prevented or reversed by citrate.3. Factors VIII, XI, and XII were not altered.4. Platelets became less adhesive and less subject to aggregation.These effects were more marked with unfiltered suspensions of thorium dioxide (TDS) than with filtered suspensions (Thorotrast). They were also increased by increasing the concentration of thorium dioxide, and the time and temperature of incubation. Thorium dioxide probably forms complexes with the clotting proteins, thereby making them less reactive.